Method for forming perovskite thin film
Patent Information
- Application Number
- KR1020240085453
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-06-28
- Filing Date
- 2024-06-28
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2044-06-28
Smart Images

Figure 112024070491797-PAT00002_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for forming a perovskite thin film, and more specifically, to a method for forming a perovskite thin film characterized by controlling the crystal growth of an all-inorganic perovskite thin film by utilizing a two-dimensional aromatic carbon chain material. Background Technology
[0002] Conventional all-inorganic perovskite thin film technology had several limitations in terms of electronic conductivity, stability, and optical properties.
[0003] In particular, existing technologies face difficulties in effectively controlling the crystal growth direction and charge transfer rate of perovskite thin films, which leads to limitations in the electron transport efficiency and long-term stability of perovskite-based solar cells.
[0004] More specifically, in conventional all-inorganic perovskite thin film technology, first, there are difficulties in effectively controlling the crystal growth direction, which leads to problems such as the optimization of charge transfer paths and electron transport losses.
[0005] Furthermore, conventional all-inorganic perovskite thin films have a problem in that their low electron conductivity limits charge transport speed, which leads to limitations resulting in reduced electron transport efficiency in optoelectronic devices such as solar cells.
[0006] Furthermore, conventional all-inorganic perovskite thin films may experience stability issues when exposed to heat, humidity, and light, which limits long-term device stability and lifespan. Prior art literature
[0007] Republic of Korea Registered Patent No. 10-2398179 The problem to be solved
[0008] The technical problem that the present invention aims to solve is to provide a method for forming a perovskite thin film characterized by controlling the crystal growth of an all-inorganic perovskite thin film by utilizing a two-dimensional aromatic carbon chain material, as a method to solve the problem of the background technology described above.
[0010] The technical problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned technical problems will be clearly understood by those skilled in the art to which the present invention belongs from the description below. means of solving the problem
[0012] To achieve the above technical problem, one embodiment of the present invention provides a method for forming a perovskite thin film.
[0013] The method for forming a perovskite thin film according to one embodiment of the present invention is,
[0014] A method for forming a perovskite thin film may be characterized by comprising: a step of dissolving a perovskite precursor and a two-dimensional aromatic carbon chain material in a solvent to form a perovskite solution; a step of coating the formed perovskite solution onto a target layer to form a first perovskite thin film layer; a step of performing a first heat treatment on the coating layer to form a second perovskite thin film layer; and a step of performing a second heat treatment on the second perovskite thin film layer to form an alpha-phase perovskite thin film layer.
[0016] In addition, according to one embodiment of the present invention, there may be a method for forming a perovskite thin film characterized in that the perovskite precursor is a material for forming an all-inorganic perovskite material having the composition of the following chemical formula 1.
[0017] [Chemical Formula 1]
[0018] ABX3
[0019] The above A is any one selected from the group consisting of Li, Na, K, Rb, Cs, and combinations thereof, the above B is any one selected from the group consisting of Pb, Sn, Ge, Ba, Mg, and combinations thereof, and the above X is any one or more selected from the group consisting of halide anions.
[0021] In addition, according to one embodiment of the present invention, there may be a method for forming a perovskite thin film characterized in that the two-dimensional aromatic carbon chain material is phenyl ammonium iodide (PEAI).
[0023] In addition, according to one embodiment of the present invention, there may be a method for forming a perovskite thin film characterized in that the two-dimensional aromatic carbon chain material is contained in the entire perovskite solution at a molar concentration of 0.001 M to 0.01 M.
[0025] In addition, according to one embodiment of the present invention, there may be a method for forming a perovskite thin film characterized in that the solvent comprises dimethyl sulfoxide (DMSO) and N, N-dimethylformamide (DMF).
[0027] In addition, according to one embodiment of the present invention, there may be a method for forming a perovskite thin film characterized in that the step of forming the perovskite solution includes the step of stirring for 10 to 14 hours at a temperature range of 22 ℃ to 27 ℃.
[0028] In addition, according to one embodiment of the present invention, the step of forming the first perovskite thin film layer may be characterized by using one or more methods selected from the group consisting of spin coating, spray coating, bar coating, and a roll-to-roll process.
[0030] In addition, according to one embodiment of the present invention, the step of forming the second perovskite thin film layer may be a method for forming a perovskite thin film characterized by performing a first heat treatment of the coating layer using a dynamic hot air treatment method.
[0032] In addition, according to one embodiment of the present invention, the dynamic hot air treatment method may be a method for forming a perovskite thin film characterized by being carried out for 5 seconds to 20 seconds at a temperature range of 200 ℃ to 300 ℃.
[0034] In addition, according to one embodiment of the present invention, there may be a method for forming a perovskite thin film, wherein the step of forming the alpha-phase perovskite thin film layer is characterized by annealing the second perovskite thin film layer and performing a second heat treatment.
[0036] In addition, according to one embodiment of the present invention, there may be a method for forming a perovskite thin film characterized by performing the annealing for 5 to 20 minutes at a temperature range of 220°C to 320°C. Effects of the invention
[0038] According to one embodiment of the present invention, a method for forming a perovskite thin film can be provided, characterized by controlling the crystal growth of an all-inorganic perovskite thin film by utilizing a two-dimensional aromatic carbon chain material.
[0039] According to one embodiment of the present invention, the crystal growth direction of an all-inorganic perovskite thin film can be effectively controlled by introducing a two-dimensional aromatic carbon chain material.
[0040] According to one embodiment of the present invention, by controlling the crystal growth of an all-inorganic perovskite thin film through the two-dimensional aromatic carbon chain material, the charge transport path can be optimized and internal defects reduced, thereby improving electron transport efficiency.
[0041] According to one embodiment of the present invention, the introduction of a two-dimensional aromatic carbon chain material forms a uniform perovskite thin film, thereby improving the stability of the all-inorganic perovskite thin film against heat, humidity, and light.
[0042] According to one embodiment of the present invention, an efficient and stable all-inorganic perovskite thin film is manufactured as described above, and an optoelectronic device with improved performance can be provided by applying the all-inorganic perovskite thin film.
[0044] The effects of the present invention are not limited to the effects described above, and should be understood to include all effects that can be inferred from the configuration of the invention described in the detailed description of the invention or the claims. Brief explanation of the drawing
[0046] FIG. 1 is a structural formula showing an example structure of a two-dimensional aromatic carbon chain material utilized in one embodiment of the present invention. FIG. 2 is a schematic diagram illustrating the process of a method for forming a perovskite thin film according to one embodiment of the present invention in sequence. FIG. 3 is a schematic diagram showing the mechanism of action of a two-dimensional aromatic carbon chain material utilized in one embodiment of the present invention. FIG. 4 is an actual photograph showing the crystal growth rate delay effect of an all-inorganic perovskite in a perovskite thin film formation method according to one embodiment of the present invention. FIG. 5 is an FE-SEM image of the surface of a perovskite thin film formed by a method for forming a perovskite thin film according to various embodiments of the present invention and a conventional method for forming a perovskite thin film, respectively. FIG. 6 is a graph showing the XRD analysis results of a perovskite thin film formed by a method for forming a perovskite thin film according to one embodiment of the present invention and a conventional method for forming a perovskite thin film. FIG. 7 is a graph comparing the light absorption and photoluminescence according to wavelength of a perovskite thin film formed by a method for forming a perovskite thin film according to one embodiment of the present invention and a conventional method for forming a perovskite thin film, respectively. FIG. 8 is a graph showing the current density according to voltage of an optoelectronic device to which a perovskite thin film formed by a method for forming a perovskite thin film according to one embodiment of the present invention and a conventional method for forming a perovskite thin film are applied, respectively. FIG. 9 is a graph showing the results of a comparative analysis of the performance of a solar cell to which a perovskite thin film formed by a method for forming a perovskite thin film according to one embodiment of the present invention and a perovskite thin film formed by a conventional method for forming a perovskite thin film are applied. FIG. 10 is a graph showing the results of comparing the stability of a perovskite thin film formed by a method for forming a perovskite thin film according to one embodiment of the present invention and a perovskite thin film formed by a conventional method for forming a perovskite thin film. Specific details for implementing the invention
[0047] The present invention will be described below with reference to the attached drawings. However, the present invention may be implemented in various different forms and is therefore not limited to the embodiments described herein. Furthermore, in order to clearly explain the present invention in the drawings, parts unrelated to the explanation have been omitted, and similar parts throughout the specification have been given similar reference numerals.
[0048] Throughout the specification, when it is stated that a part is "connected (connected, in contact, combined)" with another part, this includes not only cases where they are "directly connected," but also cases where they are "indirectly connected" with other members interposed between them. Furthermore, when it is stated that a part "includes" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but rather allows for the inclusion of additional components.
[0049] The terms used herein are merely for describing specific embodiments and are not intended to limit the invention. Singular expressions include plural expressions unless the context clearly indicates otherwise. In this specification, terms such as “comprising” or “having” are intended to indicate the presence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.
[0051] Embodiments of the present invention will be described in detail below with reference to the attached drawings.
[0052] FIG. 1 is a structural formula showing an example structure of a two-dimensional aromatic carbon chain material utilized in one embodiment of the present invention.
[0053] FIG. 2 is a schematic diagram illustrating the process of a method for forming a perovskite thin film according to one embodiment of the present invention in sequence.
[0054] FIG. 3 is a schematic diagram showing the mechanism of action of a two-dimensional aromatic carbon chain material utilized in one embodiment of the present invention.
[0055] A method for forming a perovskite thin film according to one embodiment of the present invention is described with reference to FIGS. 1 to 3.
[0057] As an example of the above embodiment, there may be a method for forming a perovskite thin film characterized by comprising: a step of dissolving a perovskite precursor and a two-dimensional aromatic carbon chain material in a solvent to form a perovskite solution; a step of coating the formed perovskite solution onto a target layer to form a first perovskite thin film layer; a step of performing a first heat treatment on the coating layer to form a second perovskite thin film layer; and a step of performing a second heat treatment on the second perovskite thin film layer to form an alpha-phase perovskite thin film layer.
[0059] As described above, by adding the two-dimensional aromatic carbon chain material to the perovskite precursor to form the perovskite solution, the crystal growth of the perovskite thin film can be effectively controlled.
[0060] At this time, the above two-dimensional aromatic carbon chain material can control the crystal growth direction of the perovskite thin film to increase electron conductivity and charge transfer rate, and improve optoelectronic performance and stability.
[0062] Referring to FIG. 1, through the example structure of the two-dimensional aromatic carbon chain material, it can be seen that the two-dimensional aromatic carbon chain material is composed of an aromatic portion, a carbon chain portion, and a functional group portion.
[0063] The above two-dimensional aromatic carbon chain material has a significantly high boiling point because it contains aromatics.
[0064] In the case of phenyl ammonium iodide exemplified in Figure 1 above, it generally has a high boiling point of 240°C to 250°C.
[0065] Referring to FIGS. 2 and 3, all hydrogen atoms (H) present in the aromatic portion, carbon chain portion, and functional group portion are halide anions (I) of the perovskite precursor material. - , Br -It can be confirmed that it interacts with (etc.) and can slow down the crystal growth rate of perovskite thin films.
[0066] First, the growth process of a perovskite thin film involves the nucleation and crystal growth stages.
[0068] If the number of nuclei formed increases during the above nucleation stage, the thin film consists of small crystals, and because there are many nuclei, crystals can grow in relatively various directions.
[0070] Conversely, if the crystal growth rate is too fast during the crystal growth step, the crystals will not grow in a consistent direction and will grow randomly, resulting in a thin film of poor quality.
[0072] Taking spin coating, which is a coating method corresponding to one example of the above embodiment, as an example, a solution is sprayed onto a substrate, and as the solution is spread thinly through high-speed rotation, the evaporation of the solution occurs.
[0073] At this stage, nucleation and crystal growth begin, and to obtain excellent perovskite thin films, a good balance between nucleation and crystal growth is required.
[0075] In conventional processes, there was a problem where crystals could not grow in a consistent direction due to the excessively fast crystal growth rate.
[0076] To solve the above problem, in the above embodiment, by introducing an aromatic carbon chain material, the crystal growth rate is slowed down and a balance is maintained with nucleation, thereby enabling control of the crystal growth direction.
[0078] Referring to FIG. 2, it can be seen that the first perovskite thin film layer is in a stage before perovskite crystals are formed, and that the perovskite precursor material and the two-dimensional aromatic carbon chain material are each dissolved.
[0079] Additionally, referring to FIG. 2, it can be confirmed that the second perovskite thin film layer formed thereafter has perovskite crystals partially formed by performing a first heat treatment on the first perovskite thin film layer. The second perovskite thin film layer is a kind of intermediate phase, in which all hydrogen atoms (H) present in the aromatic portion, carbon chain portion, and functional group portion of the two-dimensional aromatic carbon chain material are halide anions (I) of the partially formed perovskite crystals. - , Br - It can be confirmed that it is interacting with (etc.).
[0081] The interaction between the above hydrogen atom and the halide anion can occur through hydrogen bonding.
[0083] Generally, in the case of perovskite crystal growth, partially formed perovskite crystals act as nuclei in the crystal growth process and proceed through mutual interaction.
[0084] Unlike the above embodiment of the present invention, if the above two-dimensional aromatic carbon chain material were absent, the perovskite crystal growth described above could proceed more rapidly, but
[0085] In the above embodiment of the present invention, all hydrogen atoms (H) present in the aromatic portion, carbon chain portion, and functional group portion of the two-dimensional aromatic carbon chain material are halide anions (I) of the partially formed perovskite crystal. - , Br -Since it already has interactions with (etc.), it can interfere with the interactions between the partially formed perovskite crystals and ultimately delay the growth of the perovskite crystals.
[0086] The step of forming the alpha-phase perovskite (α-perovskite) thin film layer is carried out by performing a second heat treatment on the second perovskite thin film layer, through which the two-dimensional aromatic carbon chain material is evaporated, and finally, an alpha-phase perovskite (α-perovskite) thin film layer in which perovskite crystals are fully grown can be formed.
[0087] As described above, since the two-dimensional aromatic carbon chain material contains an aromatic molecular structure having a large size, it basically has a high evaporation temperature and boiling point, so it disappears relatively slowly even in the second heat treatment step, thereby allowing the growth rate of the perovskite crystal to be further slowed down.
[0089] As an example of the above embodiment, there may be a method for forming a perovskite thin film characterized in that the perovskite thin film has a perovskite composition in which all constituent elements are inorganic-based.
[0091] First of all, there are two main reasons why perovskites with all-weapon compositions are being researched.
[0092] Representative features include the fact that it is suitable for application as a tandem solar cell because it has a wide bandgap; and the fact that it can ensure long-term stability because it is inorganic-based and stable against light (ultraviolet rays, etc.).
[0094] Based on the process used in the present invention, there is a difference in the process for crystal growth between inorganic-based perovskites and organic-based perovskites.
[0096] In one example of the above embodiment of the present invention, the process of forming an inorganic-based perovskite thin film is characterized by including a process of forming a second perovskite thin film layer by performing a first heat treatment using a dynamic hot air treatment method during the process of forming the inorganic-based perovskite thin film.
[0097] In the case of organic-based perovskite thin films, since an anti-solvents process rather than dynamic hot air treatment is essential in the above process,
[0098] The above embodiment is significant in that it is a method for forming a perovskite thin film of all-inorganic composition.
[0100] In addition, organic-based perovskites generally require low heat treatment temperatures (below 150°C), and there is a problem where the thin film is damaged if temperatures higher than that are applied. Consequently, there is also a problem where the introduced aromatic carbon chain material cannot evaporate. This is because the evaporation temperature of organic-based perovskites is lower than that of aromatic carbon chains.
[0102] As an example of the above embodiment, there may be a method for forming a perovskite thin film characterized in that the perovskite precursor is a material for forming an all-inorganic perovskite material having the composition of Chemical Formula 1 below.
[0103] [Chemical Formula 1]
[0104] ABX3
[0105] The above A is any one selected from the group consisting of Li, Na, K, Rb, Cs, and combinations thereof, the above B is any one selected from the group consisting of Pb, Sn, Ge, Ba, Mg, and combinations thereof, and the above X is any one or more selected from the group consisting of halide anions.
[0107] More preferably, as an example of the above embodiment, the perovskite precursor is CsPbI 3-x Br x (The above x may have a value from 0 to 2), and
[0108] More specifically, there may be a method for forming a perovskite thin film characterized in that the perovskite precursor is a material for forming one or more all-inorganic perovskite materials selected from the group consisting of CsPbI3, CsPbI2Br, CsPbIBr2, and combinations thereof.
[0110] As an example of the above embodiment, there may be a method for forming a perovskite thin film characterized in that the perovskite precursor comprises CsI, CsBr, PbI2, and PbBr2.
[0112] As an example of the above embodiment, there may be a method for forming a perovskite thin film characterized in that the two-dimensional aromatic carbon chain material is one or more selected from the group consisting of phenylemanium iodide (PEAI), phenylemanium bromide (PEABr), phenylemanium chloride (PEACl), 4-fluoroemanium iodide (4FPEAI), 4-fluoroemanium bromide (4FPEABr), 4-fluoroemanium chloride (4FPEACl), phenylemanium thiocyanate (PEASCN), 4-methoxyemanium iodide (MeO-PEAI), 4-methoxyemanium bromide (MeO-PEABr), and 4-methoxyemanium chloride (MeO-PEACl).
[0113] Referring to FIG. 1, the structure of phenyl ammonium iodide (PEAI), which is an example of the above embodiments, can be seen.
[0114] Although the following description is based on the above-mentioned phenyl ammonium iodide (PEAI), the embodiments of the present invention are not limited to the above-mentioned phenyl ammonium iodide (PEAI), and
[0115] Substances such as the aforementioned phenylammonium bromide (PEABr), phenylammonium chloride (PEACl), 4-fluoro-phenylammonium iodide (4FPEAI), 4-fluoro-phenylammonium bromide (4FPEABr), 4-fluoro-phenylammonium chloride (4FPEACl), phenylammonium thiocyanate (PEASCN), 4-methoxy-phenylammonium iodide (MeO-PEAI), 4-methoxy-phenylammonium bromide (MeO-PEABr), and 4-methoxy-phenylammonium chloride (MeO-PEACl) can also have the same effect based on the same principle.
[0117] Referring to FIG. 2, in the step of forming the second perovskite thin film layer, which is an intermediate phase, by first heat treating the first perovskite thin film layer, all hydrogen atoms (H) present in the benzene portion, carbon chain portion, and functional group portion of the phenylalanide (PEAI) are halide anions (I) of the partially formed perovskite crystal. - , Br - It can be confirmed that hydrogen bonds are formed with (etc.).
[0118] It can be confirmed that through hydrogen bonding between the hydrogen atoms of the phenyl ammonium iodide (PEAI) and the halide anions of the partially formed perovskite crystals, the interaction between the partially formed perovskite crystals is disrupted, ultimately delaying the growth of the perovskite crystals.
[0120] Furthermore, the above-mentioned phenyl ammonium iodide (PEAI) is PEA in the perovskite precursor solution. + and I - It exists in an ionized state, and if a halogen element used in the perovskite is used in the anion site, it also has the effect of filling the halogen defects (halide vacancies) that may occur during the perovskite crystal growth process.
[0121] For example, even if defects in some I atoms occur during the crystal growth process of a perovskite having the composition CsPbI2Br, as can be seen in FIG. 2, the Pb of the perovskite material 2+ The substance and I of the above phenyl ammonium iodide (PEAI) - Through interactions between substances, I of the above phenyl ammonium iodide (PEAI) - The above-mentioned halide vacancy can be filled with a material.
[0123] As an example of the above embodiment, there may be a method for forming a perovskite thin film characterized in that the two-dimensional aromatic carbon chain material is contained in the entire perovskite solution at a molar concentration of 0.001M to 0.01M.
[0125] As described above, when the two-dimensional aromatic carbon chain material is added to the perovskite solution at a molar concentration of 0.001M to 0.01M, it is most effective for forming a high-quality perovskite thin film.
[0126] This is because, as mentioned above, the balance between nucleation and crystal growth rates is very important to obtain high-quality perovskite thin films.
[0127] If too little of the above-mentioned two-dimensional aromatic carbon chain material is introduced, the crystal growth rate is not sufficiently delayed; conversely, if too much of the above-mentioned two-dimensional aromatic carbon chain material is introduced, the crystal growth rate is delayed too much, and there is a problem that the balance with nucleation may be disrupted. Therefore, it is most desirable to form a high-quality perovskite thin film when the above-mentioned two-dimensional aromatic carbon chain material is introduced so that it can be contained in the perovskite solution at a molar concentration of 0.001M to 0.01M.
[0129] The critical significance of the concentration range of the above-described two-dimensional aromatic carbon chain material can be confirmed through the following experimental examples.
[0131] As an example of the above embodiment, there may be a method for forming a perovskite thin film characterized in that the solvent comprises dimethyl sulfoxide (DMSO) and N, N-dimethylformamide (DMF).
[0132] As an example of the above embodiment, there may be a method for forming a perovskite thin film characterized in that the solvent contains the dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF) in a volume ratio of 6:4 to 8:2.
[0134] The reason the above DMSO and DMF are used as solvents to fabricate perovskite thin films through a solution process is,
[0135] First, for the solution process, the materials used for perovskites (CsI, CsBr, PbI2, PbBr2, etc.) must dissolve in the solvent. Since these materials do not dissolve completely if the proportion of DMF is high, the proportion of DMSO must be high.
[0136] Secondly, this is because controlling the nucleation and crystal growth processes requires not only an appropriate evaporation rate but also significant interaction with the materials used to prepare the perovskite solution (such as CsI, CsBr, PbI2, and PbBr2). In particular, DMSO exhibits characteristics of very strong interaction compared to DMF. Therefore, using excessive amounts of DMSO limits nucleation.
[0137] Therefore, an appropriate volume ratio of DMSO and DMF is required, and as in the above example,
[0138] It is most preferable that the above dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF) are included in a volume ratio of 6:4 to 8:2.
[0140] As an example of the above embodiment, there may be a method for forming a perovskite thin film characterized in that the step of forming the perovskite solution includes the step of stirring for 10 to 14 hours at a temperature range of 22 ℃ to 27 ℃.
[0142] The duration of the stirring step described above is related to whether the material used (CsI, CsBr, PbI2, PbBr2, etc.) has been completely dissolved and undergone the ionization process.
[0143] The most suitable conditions for perovskite crystal growth are molecules with a BX6 structure interacting with DMSO and A + It is a state composed of ions.
[0144] At this stage, the more stirring is performed, the higher the probability of reaching the above state; however, there is also a risk that the solution may oxidize if too much time passes after the perovskite solution is prepared.
[0145] Therefore, all perovskite solutions have an appropriate stirring time, which varies depending on the composition, and for the composition used in the above example, it is most preferable to carry out the stirring step for 10 to 14 hours.
[0147] As an example of the above embodiment, there may be a method for forming a perovskite thin film characterized by using one or more methods selected from the group consisting of spin coating, spray coating, bar coating, and a roll-to-roll process for the step of forming the first perovskite thin film layer.
[0149] As an example of the above embodiment, the step of forming the second perovskite thin film layer may be a method for forming a perovskite thin film characterized by performing a first heat treatment of the coating layer using a dynamic hot air treatment method.
[0150] As an example of the above embodiment, the Dynamic hot air treatment method may be a method for forming a perovskite thin film characterized by being carried out for 5 seconds to 20 seconds in a temperature range of 200 ℃ to 300 ℃.
[0152] In the above dynamic hot air treatment method, hot air under optimal conditions partially evaporates the DMSO solvent and forms an intermediate phase, and subsequently, the intermediate phase is finally converted into alpha-phase perovskite through annealing.
[0153] At this time, the temperature and time conditions of the above-mentioned Dynamic hot air treatment method are related to the crystal growth rate and nucleation.
[0154] The above hot air treatment method is used to create an intermediate phase of the desired level. However, if the temperature is too low (below 200°C) or the time is too short (below 5 seconds), a problem arises where the DMSO cannot evaporate as much as desired.
[0155] Conversely, if the process is performed for too long, exceeding 20 seconds, crystal growth may be promoted, resulting in an annealing process similar to that performed in a temperature range below 200°C. Furthermore, if hot air treatment is performed at a temperature exceeding 300°C, there is a problem in that the intermediate phase is skipped and the alpha phase is formed, resulting in a very low-quality thin film.
[0157] As an example of the above embodiment, there may be a method for forming a perovskite thin film, wherein the step of forming the alpha-phase perovskite thin film layer is characterized by annealing the second perovskite thin film layer to perform a second heat treatment.
[0158] As an example of the above embodiment, there may be a method for forming a perovskite thin film characterized by performing the annealing for 5 to 20 minutes at a temperature range of 220°C to 320°C.
[0159] More preferably, as an example of the above embodiment, there may be a method for forming a perovskite thin film characterized by performing the annealing for 5 to 20 minutes at a temperature range of 240°C to 280°C.
[0161] The aforementioned annealing refers to the process of heating a material at a high temperature for an extended period to control and improve its structure or physical properties.
[0162] In the above embodiment of the present invention, the goal is to control the growth rate of the perovskite crystal by appropriately evaporating the two-dimensional aromatic carbon chain material that hinders the growth of the perovskite crystal through the annealing process.
[0163] That is, in order to achieve the above objective of the present invention, the temperature at which the annealing is performed is important. Below, the critical significance of the annealing temperature is explained using the case where phenyl ammonium iodide (PEAI) is used as the two-dimensional aromatic carbon chain material as an example.
[0165] If the annealing is performed at a temperature below 220°C, the phenyl ammonium iodide (PEAI) begins to boil at approximately 240°C to 250°C, so the problem arises that the PEAI is not effectively removed.
[0166] In addition, in the case of CsPbI2Br among the perovskite compositions corresponding to the above example, since an appropriate level of thermal energy (240°C or higher) must be applied for substitution into the alpha phase, there is a problem that it is impossible to obtain an alpha phase perovskite thin film at a temperature of 220°C or lower.
[0168] On the other hand, if the annealing is performed at a temperature exceeding 320°C, the phenyl ammonium iodide (PEAI) is removed too quickly, resulting in a problem where the growth of the perovskite crystal is not sufficiently delayed.
[0169] Furthermore, applying excessively high temperatures is inappropriate because, aside from the removal of the aforementioned PEAI, it causes the perovskite thin film itself to collapse.
[0171] When the direction and speed of the perovskite crystal growth are effectively controlled as described above,
[0172] It is possible to optimize charge transport paths and further reduce internal defects in perovskite thin films, thereby improving electron transport efficiency, and
[0173] By forming a more uniform perovskite thin film, the stability of the perovskite thin film against heat, humidity, and light can be improved, and
[0174] As described above, the perovskite thin film with improved electron transport efficiency and stability has the advantage of ultimately enhancing the performance of optoelectronic devices to which the perovskite thin film is applied.
[0177] Comparative Preparation Example 1. Conventional perovskite solution formation step.
[0179] The following process is performed to form a perovskite solution having a composition of 1.2M CsPbI2Br.
[0181] 1. As a perovskite precursor material, 311.8 mg of CsI powder, 276.6 mg of PbI2 powder, and 220.2 mg of PbBr2 powder are provided.
[0182] 2. The perovskite precursor prepared above is placed in a mixed solution of 0.7 ml of dimethyl sulfoxide (DMSO) and 0.3 ml of N, N-dimethylformamide (DMF), and stirred for 12 hours.
[0184] Preparation Example 1. Step of forming a perovskite solution with added two-dimensional aromatic carbon chain material (0.4 mg).
[0186] 1. As a perovskite precursor material, 311.8 mg of CsI powder, 276.6 mg of PbI2 powder, and 220.2 mg of PbBr2 powder are provided.
[0187] 2. The perovskite precursor prepared above is placed in a mixed solution of 0.7 ml of dimethyl sulfoxide (DMSO) and 0.3 ml of N, N-dimethylformamide (DMF) together with 0.4 mg of phenyl ammonium iodide (PEAI) powder, and stirred for 12 hours.
[0189] Preparation Example 2. Step of forming a perovskite solution with added two-dimensional aromatic carbon chain material (0.8 mg).
[0191] 1. As a perovskite precursor material, 311.8 mg of CsI powder, 276.6 mg of PbI2 powder, and 220.2 mg of PbBr2 powder are provided.
[0192] 2. The perovskite precursor prepared above is placed in a mixed solution of 0.7 ml of dimethyl sulfoxide (DMSO) and 0.3 ml of N, N-dimethylformamide (DMF) together with 0.8 mg of phenyl ammonium iodide (PEAI) powder, and stirred for 12 hours.
[0193] Preparation Example 3. Step of forming a perovskite solution with added two-dimensional aromatic carbon chain material (1.2 mg).
[0195] 1. As a perovskite precursor material, 311.8 mg of CsI powder, 276.6 mg of PbI2 powder, and 220.2 mg of PbBr2 powder are provided.
[0196] 2. The perovskite precursor prepared above is placed in a mixed solution of 0.7 ml of dimethyl sulfoxide (DMSO) and 0.3 ml of N, N-dimethylformamide (DMF) together with 1.2 mg of phenyl ammonium iodide (PEAI) powder, and stirred for 12 hours.
[0199] Experimental Example 1. Experiment on controlling the growth rate of perovskite crystals.
[0200] FIG. 4 is an actual photograph showing the crystal growth rate delay effect of an all-inorganic perovskite in a perovskite thin film formation method according to one embodiment of the present invention.
[0201] The above experimental example is explained with reference to Fig. 4.
[0202] Figure 4 above shows the process of crystallization proceeding without the first heat treatment (hot air treatment) and the second heat treatment (annealing at 240°C).
[0204] Referring to FIG. 4, the crystallization process when using the perovskite solution (without PEAI) prepared in Comparative Example 1 above can be compared with the crystallization process when using the perovskite solution (with PEAI) prepared in Comparative Example 1 above.
[0205] When examining the crystallization process when using the perovskite solution (without PEAI) prepared in Comparative Preparation Example 1 above, discoloration is observed after 120 min, but
[0206] When examining the crystallization process when using the perovskite solution (containing PEAI) prepared in Preparation Example 1 above, discoloration is observed after 150 min.
[0207] In other words, a delay effect of about 30 minutes in the growth rate of perovskite crystals can be observed.
[0209] Experimental Example 2. Improvement of physical properties of perovskite thin films.
[0210] FIG. 5 is an FE-SEM image of the surface of a perovskite thin film formed by a method for forming a perovskite thin film according to various embodiments of the present invention and a conventional method for forming a perovskite thin film, respectively.
[0211] FIG. 6 is a graph showing the XRD analysis results of a perovskite thin film formed by a method for forming a perovskite thin film according to one embodiment of the present invention and a conventional method for forming a perovskite thin film.
[0212] FIG. 7 is a diagram comparing the light absorption and photoluminescence according to wavelength of a perovskite thin film formed by a method for forming a perovskite thin film according to one embodiment of the present invention and a conventional method for forming a perovskite thin film, respectively.
[0213] FIG. 8 is a graph showing the current density according to voltage of an optoelectronic device to which a perovskite thin film formed by a method for forming a perovskite thin film according to one embodiment of the present invention and a conventional method for forming a perovskite thin film are applied, respectively.
[0214] The above experimental example is explained with reference to the above Figures 5 to 8.
[0216] Referring to FIG. 5, compared to the case of forming a perovskite thin film in a conventional manner,
[0217] When a perovskite thin film is formed using PEAI according to one embodiment of the present invention, it can be confirmed that fewer surface defects (pinholes) exist.
[0218] In the case of perovskite thin films formed by conventional methods, a very large number of pinholes can be observed on average, but
[0219] As in the embodiment of the present invention, when 0.4 mg of PEAI is added, it can be confirmed that on average only one pinhole is formed in the same area, and
[0220] When 0.8 mg of the above PEAI is added, a uniformly formed perovskite thin film without pinholes can be observed.
[0221] At this time, when the above PEAI is increased to 1.2 mg, it can be confirmed that there are no pinholes, but some defects (defective surface) exist on the surface.
[0223] Therefore, the most optimal amount of PEAI added is 0.8 mg, which corresponds to a concentration of about 0.00366 M for the perovskite solution.
[0224] When 0.4 mg of PEAI is added, the value corresponds to a concentration of approximately 0.00183 M for the perovskite solution, and when 1.2 mg of PEAI is added, the value corresponds to a concentration of approximately 0.00549 M for the perovskite solution.
[0226] Referring to FIG. 6, it can be seen that the peak of a perovskite thin film formed by a conventional perovskite thin film formation method and the peak of a perovskite thin film formed by a perovskite thin film formation method according to one embodiment of the present invention are basically formed at the same location.
[0227] However, referring to Fig. 6 above,
[0228] It can be seen that the peaks of the perovskite thin film formed by the conventional perovskite thin film formation method show an intensity of 37554 at (100) and an intensity of 36057 at (200).
[0230] On the other hand, it can be seen that the peak of the perovskite thin film formed by the method of forming a perovskite thin film according to one embodiment of the present invention shows an intensity of 46175 at (100) and an intensity of 48857 at (200).
[0232] As described above, it can be confirmed that the perovskite thin film formed by the perovskite thin film formation method according to one embodiment of the present invention has a higher intensity, which means that the perovskite thin film formed by the perovskite thin film formation method according to one embodiment of the present invention has superior crystallinity compared to the comparison subject.
[0234] Referring to FIG. 7, the light absorption and photoluminescence according to wavelength of a perovskite thin film formed by a method for forming a perovskite thin film according to one embodiment of the present invention and a perovskite thin film formed by a conventional method for forming a perovskite thin film can be compared.
[0235] Referring to FIGS. 7a and 7b, it can be seen that a perovskite thin film formed by the perovskite thin film formation method according to one embodiment of the present invention has superior values compared to a comparison subject for both light absorption and photoluminescence in the entire wavelength range.
[0237] Figures 8a and 8b show the results of space-charge-limited current (SCLC) analysis, which is used to compare defects in perovskite solar cells.
[0238] At this time, through the measurement results of the space charge-limiting current of the above perovskite solar cell, V TFL You can check the (trap filled limit voltage),
[0239] The above V TFL (trap filled limit voltage) explains the phenomenon in which trap states in electronic devices limit charge movement,
[0240] More specifically, as the voltage increases, more charge is injected into the device, and this charge fills the defects within the device. Consequently, even if the voltage is raised, the increase in current does not become very high.
[0241] Once the defect is fully filled, there is no longer any charge being drawn toward the defect, so the current rises suddenly. The voltage at the point where the current rises suddenly is V. TFL It is called.
[0242] Therefore, the above V TFL The lower this value, the fewer defects there are, and
[0243] Referring to FIG. 8, V of an optoelectronic device to which a perovskite thin film formed by a perovskite thin film formation method according to an embodiment of the present invention is applied TFL The value is 0.51V, and the V of the optoelectronic device to which the perovskite thin film formed by the conventional perovskite thin film formation method is applied. TFL Since the value is 0.92V,
[0244] It can be confirmed that the defects of the optoelectronic device to which the perovskite thin film formed by the perovskite thin film formation method according to one embodiment of the present invention is applied are fewer.
[0246] Experimental Example 3. Performance analysis of a solar cell with a perovskite thin film.
[0248] FIG. 9 is a graph showing the results of a comparative analysis of the performance of a solar cell to which a perovskite thin film formed by a method for forming a perovskite thin film according to one embodiment of the present invention and a perovskite thin film formed by a conventional method for forming a perovskite thin film are applied.
[0249] FIG. 10 is a graph showing the results of comparing the stability of a perovskite thin film formed by a method for forming a perovskite thin film according to one embodiment of the present invention and a perovskite thin film formed by a conventional method for forming a perovskite thin film.
[0250] The above experimental example is explained with reference to FIGS. 9 and FIGS. 10.
[0252] Referring to FIG. 9a, when examining the current density graph according to voltage, it can be confirmed that the open-circuit voltage and current density of the solar cell to which the perovskite thin film formed by the perovskite thin film formation method according to one embodiment of the present invention is applied are higher than those of the comparison subject over the entire voltage range.
[0253] In addition, referring to Fig. 9b, the External Quantum Efficiency (EQE) and Integrated J according to wavelength sc The (Total Current Density) values can be compared, and over the entire wavelength range, the EQE and J of the solar cell to which the perovskite thin film formed by the perovskite thin film formation method according to one embodiment of the present invention is applied sc It can be confirmed that the value is formed higher than the comparison target.
[0254] This means that a solar cell to which a perovskite thin film formed by the perovskite thin film formation method according to one embodiment of the present invention is applied has superior performance compared to a comparative subject.
[0256] Referring to Fig. 10, the Normalized PCE graphs over time can be compared.
[0257] The aforementioned Normalized Power Conversion Efficiency (Normalized PCE) is one of the indicators used to easily compare the efficiency of solar cells. PCE is used to measure the ability to convert solar energy into electricity, and Normalized PCE is used to normalize this efficiency to obtain a relative measurement value for comparison under different conditions.
[0258] Referring to the experimental data in FIG. 10, it can be confirmed that a solar cell to which a perovskite thin film formed by the perovskite thin film formation method according to one embodiment of the present invention is applied has a superior Normalized PCE value over time compared to a comparison subject.
[0259] This means that a solar cell to which a perovskite thin film formed by the perovskite thin film formation method according to one embodiment of the present invention is applied has improved stability compared to a comparative subject.
[0261] The foregoing description of the present invention is for illustrative purposes only, and those skilled in the art will understand that other specific forms can be easily modified without altering the technical spirit or essential features of the present invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive. For example, each component described as a single unit may be implemented in a distributed manner, and components described as distributed may likewise be implemented in a combined form.
[0262] The scope of the present invention is defined by the claims set forth below, and all modifications or variations derived from the meaning and scope of the claims and equivalent concepts thereof should be interpreted as being included within the scope of the present invention.
Claims
Claim 1 A method for forming a perovskite thin film, comprising: a step of dissolving an inorganic perovskite precursor and a two-dimensional aromatic carbon chain material in a solvent to form a perovskite solution; a step of depositing the formed perovskite solution onto a target layer to form a first perovskite thin film layer; a step of performing a first heat treatment on the first perovskite thin film layer to form a second perovskite thin film layer; and a step of performing a second heat treatment on the second perovskite thin film layer to form an alpha-phase perovskite thin film layer; wherein the second heat treatment is characterized by annealing for 5 minutes to 20 minutes at a temperature range of 220 ℃ to 320 ℃. Claim 2 A method for forming a perovskite thin film according to claim 1, wherein the perovskite precursor is a material for forming an all-inorganic perovskite material having the composition of the following chemical formula 1: [Chemical Formula 1] ABX3, wherein A is any one selected from the group consisting of Li, Na, K, Rb, Cs, and combinations thereof, B is any one selected from the group consisting of Pb, Sn, Ge, Ba, Mg, and combinations thereof, and X is any one or more selected from the group consisting of halide anions. Claim 3 A method for forming a perovskite thin film according to claim 1, wherein the two-dimensional aromatic carbon chain material is one or more selected from the group consisting of phenylemanium iodide (PEAI), phenylemanium bromide (PEABr), phenylemanium chloride (PEACl), 4-fluoroemanium iodide (4FPEAI), 4-fluoroemanium bromide (4FPEABr), 4-fluoroemanium chloride (4FPEACl), phenylemanium thiocyanate (PEASCN), 4-methoxyemanium iodide (MeO-PEAI), 4-methoxyemanium bromide (MeO-PEABr), and 4-methoxyemanium chloride (MeO-PEACl). Claim 4 A method for forming a perovskite thin film according to claim 1, characterized in that the two-dimensional aromatic carbon chain material is contained in the entire perovskite solution at a molar concentration of 0.001M to 0.01M. Claim 5 A method for forming a perovskite thin film according to claim 1, characterized in that the solvent comprises dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF). Claim 6 A method for forming a perovskite thin film according to claim 1, wherein the step of forming the perovskite solution comprises the step of stirring for 10 to 14 hours at a temperature range of 22 ℃ to 27 ℃. Claim 7 A method for forming a perovskite thin film according to claim 1, wherein the step of forming the first perovskite thin film layer is characterized by using one or more methods selected from the group consisting of spin coating, spray coating, bar coating, and a roll-to-roll process. Claim 8 A method for forming a perovskite thin film according to claim 1, wherein the step of forming the second perovskite thin film layer is characterized by performing a first heat treatment on the first perovskite thin film layer using a dynamic hot air treatment method. Claim 9 A method for forming a perovskite thin film according to claim 8, wherein the dynamic hot air treatment method is performed for 5 seconds to 20 seconds at a temperature range of 200 ℃ to 300 ℃. Claim 10 delete Claim 11 delete
Citation Information
Patent Citations
Perovskite / Gallium Arsenide tandem type solar cell and preparation method thereof
KR1020210136418A
Manufacturing method of alpha-phase perovskite crystals with high yield and Alpha-phase perovskite crystals manufactured by the method
KR1020230159658A
Method of Stabilizing the Crystal Phase of Amidinium Ion Based Perovskite Compound Layer
KR102201894B1